NEOLIBERALISM, CONSUMERISM, AND ENGLISH LANGUAGE TEACHING: A DISCOURSE ANALYSIS OF AN ENGLISH TEXTBOOK OF JUNIOR HIGH SCHOOL PEKANBARU - Melgis Dilkawaty Pratama (Indonesian Journal of Integrated English Language Teaching, 2017)
This study investigates the ideologies underlie in the English textbook of Junior High School in Pekanbaru. Those ideologies act as intended curriculum of English language teaching.However, some ideologies are contrary to the intended curriculum stated. Consequently, the English language teaching will bring wrong message to the students’ mindset. The design of this study is discourse analysis which emphasizes on linguistic and socioeconomic views. This study revealed that the English textbook used neoliberalism and consumerism as the ideologies which is contradictive to the intended curriculum stated. Therefore, the use of this English textbook needs the comprehensive guidance of teachers in interpreting and explaining the content to the students.